2020
DOI: 10.3389/fnana.2020.00007
|View full text |Cite
|
Sign up to set email alerts
|

Monosynaptic Input Mapping of Diencephalic Projections to the Cerebrospinal Fluid-Contacting Nucleus in the Rat

Abstract: Objective: To investigate the projections the cerebrospinal fluid-contacting (CSFcontacting) nucleus receives from the diencephalon and to speculate on the functional significance of these connections. Methods:The retrograde tracer cholera toxin B subunit (CB) was injected into the CSF-contacting nucleus in SD rats according to the experimental formula of the stereotaxic coordinates. Animals were perfused 7-10 days after the injection, and the diencephalon was sliced at 40 µm with a freezing microtome. CB-immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…The mean CSF volume is 150 ml, with 25 ml in the ventricles and 125 ml in subarachnoid spaces [14]. CSF-contacting neurons (CSF-N) are present in the surface of both brain ventricles and the central canal (cc) in the spinal cord [15,16] as well as specific locations [17]. The CSF-Ns sense pH changes and motion in the hypothalamus [18].…”
Section: Csf Pulsatility and Circulationmentioning
confidence: 99%
“…The mean CSF volume is 150 ml, with 25 ml in the ventricles and 125 ml in subarachnoid spaces [14]. CSF-contacting neurons (CSF-N) are present in the surface of both brain ventricles and the central canal (cc) in the spinal cord [15,16] as well as specific locations [17]. The CSF-Ns sense pH changes and motion in the hypothalamus [18].…”
Section: Csf Pulsatility and Circulationmentioning
confidence: 99%
“…It implies that the CSF-contacting nucleus may be considered as an important structure bridging the brain and CSF, or that it plays an extremely important role in physiological activities. Moreover, our recent studies reveal that this nucleus receives the projections from the hypothalamus (Song et al, 2020b ) and brainstem (Song et al, 2020a ), which implies that the CSF-contacting nucleus participates in complex and diverse neural circuits modulating different behaviors. The relationships with some of the life activities such as pain (Liu et al, 2017 ), stress (Wu et al, 2015 ), and drug addiction (Lu et al, 2011 ) have been already reported.…”
Section: Introductionmentioning
confidence: 98%
“…The CSF-contacting nucleus is believed to be a unique nucleus in the brain that participates in neuron-neuron and neuron-body fluid crosstalk, and thus possibly influences the regulation of multiple physiological processes [23][24][25][26]. Increasing evidence also suggests that the CSF-contacting nucleus mediates the transduction and regulation of pain signals and might be involved in the modulation of the descending inhibitory system [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the endocannabinoids have been demonstrated to alter the permeability of the BBB in various pain disorders [16,30]. This may be due to their action in the periventricular area that is not protected by the BBB, or to the mediation of the function of the CSFcontacting nucleus [16,24,25,31]. We presumed that AEA and 2-AG synthesized in the brain tissue are released into the CSF and may act in a competitive way to regulate the function of the brain centers located in the vicinity of the cerebral ventricles and the fundus of the fourth ventricle, where the sensory and motor centers of the tested trigemino-hypoglossal reflex are located [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%